Penerapan Algoritme Basic Theta* Pada Game Hexaconquest - Ilman Naafian Firmansyah; Eriq Muhmmad Adams Jonemaro; Muhammad Aminul Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Nearly every Turn-based Strategy Games today have a singleplayer feature in their Game modes. If there is only one human player, then every other player must be controlled by computer. This is where AI(Artificial Intelligence) used. AI used so the Game can be played by a human player as if they play against another human. Human player can then use this feature to train their playing skill while playing against computer player before they play against another human player. Commonly used algorithm to search for most optimal way AI can use to reach their destination is A* algorithm. But A* is not always the best solution for pathfinding. In this study we try to implement Basic Theta* algorithm on a Turn-based Strategy Game called Hexaconquest. Basic Theta* algorithm performance will then be compared to Hexaconquest's original pathfinding algorithm, A*. Both algorithm frame per second, running time, and node total cost performance will be compared. From result of this study, we can conclude that Basic Theta* algorithm can give solution with shortest route, but A* can give lighter and faster solution.